The curious incident of the boys and the bears 2 Kings 2 and the prophetic authority of Elisha - Irwin, Brian Payl 1961- (2016)
A view of 2 Kings 2 that is commonly encountered regards the cursing of the children of Bethel as a meaningless act that is beneath the dignity of the prophet. This paper argues that the curse uttered by Elisha in 2 Kings 2:24 is a covenant curse based on Leviticus 26:22 and is intended to warn Israel of what lies in store if it disregards the prophetic word. In this it complements the story of the healing of the waters of Jericho (2 Kings 2:19-22) which establishes the corollary principle. The events of 2 Kings 3–8 then illustrate this principle in a variety of contexts both nationally and internationally.
Keywords: Bears -- Religious aspects; Bible. Kings II 1-8; Bible. Kings II -- Criticism, Literary; Blessing and cursing in the Bible; Covenants -- Biblical teaching; Elisha, (Biblical prophet); Peer reviewed